TINGKAT HUTANG, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP PERSISTENSI LABA DENGAN BOOK TAX DIFFERENCE SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan LQ45 yang terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Yutri Nurmalasari; Kamaliah Kamaliah; Azwir Nasir (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
This study aims to examine and determine the effect of debt degrees, liquidity andFirm Size on the earning persistence. In addition, this study also aims to testwhether a variable tax book difference moderates the relationship between eachvariable of the debt levels, liquidity and firm size on the earning persistence. Thesample used in this study is a company registered in LQ45 Index Indonesia StockExchange (IDX) during 2015-2017. The total samples are 27 companies usingpurposive sampling technique. The method of data analysis uses moderateregression analysis (MRA) with SPSS 21 software. The results of the study showedthat whether being together or partially, the independent variable influenced thepersistence of earnings, so the higher the level of debt, liquidity, and the size of thecompany are, the more persistent the profits are. The research results concerningthe moderating variable showed that the book tax difference had an influence asmoderating variable between the level of liquidity on the earnings persistence, so thehigher book tax difference in the form of deferred tax benefit, the stronger therelationship between the level of liquidity and earnings persistence. On the reverse,the book tax difference had no impact as a moderating variable between debtdegree and the persistence of earnings as well as the firm size with earningspersistence. Thus, the load and deferred tax benefit did not strengthen or weakenthe relationship between the level of debt to earning persistence as well as the sizeof the company with earning persistence.